Product Innovation Under Vertical Differentiation and the Persistence of Monopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The incentives to innovate for the incumbent and the entrant in a vertically differentiated market are analised, in the absence of uncertainty. It turns out that if consumers' marginal willingness to pay for quality is sufficiently low, the efficiency effect observationally works so as to favour innovation by the entrant, i.e., competition. Otherwise, it operates to the advantage of the incumbent who acquire the right to innovate, preempting thus the rival.
Keywords: 330